Analisis Strategi Pemasaran Online Untuk Meningkatkan Penjualan Pada UMKM Salon Youlind di Kecamatan Wagir Kabupaten Malang - Priatma, Yulinda; Asminah Rachmi; Mohammad Maskan (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Online marketing is one of the strategies used by utilizing digital platforms to reach a broader range of customers through social media. This strategy aims to enhance promotional effectiveness and support sales growth. One of the MSMEs that has implemented this approach is Salon Youlind, located in Wagir Sub-District, Malang Regency, which operates in the beauty service sector. In its operations, Salon Youlind has used social media platforms such as WhatsApp and Instagram to expand its customer reach online. This research aims to analyze and evaluate the potential online marketing strategies to optimize promotions and expand the salon’s market coverage in a more targeted manner. This research was a qualitative study using a case study approach. The data were collected through interviews, observation, and documentation. The data collection involved 14 informants, consisting of the owner, employees, and customers. The data were analyzed using social media metrics, including awareness, engagement, and conversion metrics. The analysis showed that the implemented online marketing strategy led to increased social media interactions, broader audience reach, and had a positive impact on sales growth. Improved content consistency and the optimal use of social media platforms also contributed to greater income stability at Salon Youlind. Based on the research findings, it can be concluded that the Youlind Salon MSME has implemented a more effective marketing strategy. To optimize its digital marketing efforts, the business is expected to enhance its digital competencies, adjust content scheduling, ensure consistency in design formats, and carry out regular evaluations of social media performance as a tool to promote its beauty services.